KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA SMA - Darnita Diana (Teks: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2021)
This study aims to determine empirically the relationship of student attitudes toward Indonesian course and vocabulary comprehension with writing exposition competence in class X SMAN 4 Serang City. The study was conducted on the students of class X of the even semester of the academic year 2016/2017. The research method used in this research is survey method with correlational study approach. The population of this study is all students of class X SMAN 4 Serang City in the even semester of the academic year 2016/2017 which amounted to 428 students. Class X is chosen because in this class students have been given the subject of exposition texts. The data collection in this study is to use test instruments and questionnaires. Based on the results of research and discussion, can be drawn conclusion on the results of research as follows: 1) There is a positive and significant relationship between students attitudes toward Indonesian course with writing exposition competence; 2) There is a positive and significant relationship between vocabulary comprehension and writing exposition competence; and 3) There is a positive and significant relationship between students attitudes toward Indonesian course and vocabulary comprehension together with writing exposition.